2007
DOI: 10.1186/1472-6874-7-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of women's cancer screening and contraceptive knowledge among female emergency department patients

Abstract: BackgroundLack of knowledge regarding preventive health services for women might impede campaigns to expand these services in the emergency department setting. For 18–55-year-old English-speaking women visiting an urban emergency department, we aimed to: (1) Ascertain their knowledge regarding the applicability, purpose, and recommended intervals of three women's cancer screening and three contraceptive methods; and (2) Determine if patient age, race/ethnicity, medical insurance status, and current or recent u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Despite expenditures in the millions of dollars and national campaigns by the American Cancer Society, the National Cancer Institute, as well as the efforts of most hospitals and physicians, large segments of the population do not possess knowledge about when to obtain screening. [2][3][4] The challenge of how best to educate the public is compounded by lack of health literacy, 5 fear of procedures or what they may reveal, [6][7][8] and the deterrent cost of screening procedures for many individuals. 9 To make the issue even more complex, educational efforts may focus on very specific aspects of the population and need to appeal to individuals of a certain gender, age, or ethnic/cultural background.…”
mentioning
confidence: 99%
“…Despite expenditures in the millions of dollars and national campaigns by the American Cancer Society, the National Cancer Institute, as well as the efforts of most hospitals and physicians, large segments of the population do not possess knowledge about when to obtain screening. [2][3][4] The challenge of how best to educate the public is compounded by lack of health literacy, 5 fear of procedures or what they may reveal, [6][7][8] and the deterrent cost of screening procedures for many individuals. 9 To make the issue even more complex, educational efforts may focus on very specific aspects of the population and need to appeal to individuals of a certain gender, age, or ethnic/cultural background.…”
mentioning
confidence: 99%
“…The study by Castellsagué and Muñoz has pointed out importance of secondary preventive measures for the cervical cancer in OC users (19). Some studies, unlike ours, have found out more frequent preventive measures application in the OC users (20)(21)(22). The study by Park SJ and Park WS have found to women under hormone therapy were significantly more likely to get Pap tests and check-ups (23).…”
Section: Discussionmentioning
confidence: 47%
“…The development of the questionnaire for this study has been reported previously (Merchant et al 2007); a summary is provided here. We created a draft version of the questionnaire after reviewing numerous questionnaires from published women’s cancer screening and contraceptive health studies.…”
Section: Methodsmentioning
confidence: 99%
“…Elsewhere, we have reported our findings on these patients’ cancer screening and contraceptive knowledge (Merchant et al 2007) and preferences for women’s cancer screening and contraceptive services (Merchant et al 2007). In this manuscript, we report on a potential barrier to the successful implementation of women’s cancer screening and contraceptive programs in EDs: negative opinions by women toward Pap smears, BSEs, BCPs, and condoms.…”
mentioning
confidence: 99%